Stroke and the risk of gastrointestinal disorders: A Mendelian randomization study - Song, Jingru; Chen, Wenjing; Ye, Wei (Frontiers in Neurology, 2023)
Background The issue of whether a stroke is causally related to gastrointestinal disorders was still not satisfactorily understood. Therefore, we investigated if there is a connection between stroke and the most prevalent gastrointestinal disorders, including peptic ulcer disease (PUD), gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD). Methods We applied two-sample Mendelian randomization to investigate relationships with gastrointestinal disorders. We obtained genome-wide association study (GWAS) summary data of any stroke, ischemic stroke, and its subtypes from the MEGASTROKE consortium. From the International Stroke Genetics Consortium (ISGC) meta-analysis, we acquired GWAS summary information on intracerebral hemorrhage (ICH), including all ICH, deep ICH, and lobar ICH. Several sensitivity studies were performed to identify heterogeneity and pleiotropy, while inverse-variance weighted (IVW) was utilized as the most dominant estimate. Results No evidence for an effect of genetic predisposition to ischemic stroke and its subtypes on gastrointestinal disorders were found in IVW. The complications of deep ICH are a higher risk for PUD and GERD. Meanwhile, lobar ICH has a higher risk of complications for PUD. Conclusion This study provides proof of the presence of a brain–gut axis. Among the complications of ICH, PUD and GERD were more common and associated with the site of hemorrhage.